(untitled) - George Donelson Moss (Englewood Cliffs, New Jersey, 1990)
The book is a comprehensive narrative that depicts the history of American involvement in Southeast Asia from its genesis in the 1940s to its tragic denouement in 1975. It explains why the United States involved itselffor so long in the affairs of a seemingly small, poor, and insignificant country; why the world's richest and most powerful nation fought a long, losing war in VietNam; the political and military activities of the Vietnamese communists and a succession of governements in South VietNam backed by the United States; the major battles of the American war and the experiences of the men called to fight them; the impact this war hard on American politics, economic affairs, and culture
Keywords: vietnamese conflict, 1961-1975